Impact of foam-mat drying conditions of “Gấc” aril on drying rate and bioactive compounds: Optimization by novel statistical approaches - Nguyễn Minh Thủy; Vo Quoc Tien; Tran Ngoc Giau; Hong Van Hao; Võ Quang Minh; Ngô Văn Tài (Food Chemistry X, 2024)
This study was conducted to optimize the foam-mat drying conditions to maximize quality [β-carotene and total polyphenol content (TPC)] and drying rate of "Gấc" aril powder by using two novel statistical techniques as Response Surface Methodology (RSM) and Artificial Neural Network (ANN) couple with Genetic Algorithm (GA). During production process, level of egg albumin (EA) used for foaming process and drying temperature mainly influenced the drying rate and content of antioxidant compounds in powder. ANN model of 3-10-3 showed more accuracy and faster prediction capacity than RSM model did. ANN-GA model predicted the optimal conditions to be 13.31 % EA, 0.26 % xanthan gum and drying temperature of 73.1 °C, with the drying rate of 1.89 g-water/g-dry matter/min, β-carotene content of 395.88 μg/g, TPC of 1.68 mgGAE/g. These results confirmed the suitability and promising of foam-mat drying for "Gấc" aril powder production, to be producing food ingredient containing highly bioactive compounds.
Keywords: Food Drying and Modeling; Microencapsulation and Drying Processes; Phytochemicals and Antioxidant Activities